2010
DOI: 10.3844/ajavsp.2010.208.214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli Isolates from Commercial Layer Hens with Salpingitis

Abstract: Problem statement: Escherichia coli isolates are the most common bacterial agents of salpingitis in commercial layer hens. The objectives of this study were to determine the phylogenetic groups/subgroups and antibiotic resistance of E. coli isolates from salpingitis cases in commercial layer hens farms in southeast of Iran. Approach: One hundred twenty one E. coli isolates from oviducts of layer hens with salpingitis were examined to determine their O-serogroup, phylogenetic group/subgroup and antibiotic resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…It was detected in oviducts of commercial layers as one of the most predominant serovars in different studies (Trampel et al, 2007;Salehi andGhanbarpour, 2010 andSrinivasan et al, 2013). The serogroup O86 was deteced in salpingitis cases in this study and in study of Salehi andGhanbarpou (2010). Eidand Erfan (2013) found that, O114, O125, O55, O111 and O26 serogroups were the most prevalent in broiler flocks in Sharkia Governorate (Egypt), also these serogoups were found predominant in our study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…It was detected in oviducts of commercial layers as one of the most predominant serovars in different studies (Trampel et al, 2007;Salehi andGhanbarpour, 2010 andSrinivasan et al, 2013). The serogroup O86 was deteced in salpingitis cases in this study and in study of Salehi andGhanbarpou (2010). Eidand Erfan (2013) found that, O114, O125, O55, O111 and O26 serogroups were the most prevalent in broiler flocks in Sharkia Governorate (Egypt), also these serogoups were found predominant in our study.…”
Section: Discussionsupporting
confidence: 48%
“…The serogroups include O111, O26, O125,O55, O114, O127, O86, O124 and O142 serogroups (Table ,2). Salehi and Ghanbarpour, (2010) isolated 47 strains of E. coli from commercial layer hens with salpingitis. The isolates were typeable and belonged to 11 serogroupes (O1, O2,O6, O8, O15, O20, O25, O36, O78, O86 and O111).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotyped strains (n=40) belonged to 10 serovars, O78 (n=13), O153 (n=6), O168 (n=5), O26 (n=4), O157 and O146 (n=3 each), O20 and O114 (n=2 each), O125 and O126 (n=one each). Salehi and Ghanbarpour (2010) isolated E. coli serogroups O6, O15, O25, and O78 from oviducts of layer hens with salpingitis. Meanwhile, Kika et al (2013) isolated E. coli serogroups O15 and O115 from visceral organs of birds with colibacillosis.…”
Section: Streptococcimentioning
confidence: 99%
“…Among the different serotypes identified from impacted oviduct, serotypes O , O and O were predominant, however none of the serogroup was belongs to the systemic form serogroups such as O , O and O [26,27] . The occurrence of a specific serotype and its role in disease production depends upon the health status of the birds, climatic conditions, geographical situations and managemental strategies.…”
Section: Mycoplasma Gallisepticum Mycoplasma Synoviaementioning
confidence: 99%